FOSTERING KNOWLEDGE SHARING AMONG SOFTWARE ENGINEERS- A CASE OF MALAYSIAN SOFTWARE INDUSTRY - REHMAN, MOBASHAR (2013)
Software Engineering is a booming industry and has huge impact on world economy. This profe"ion is highly knowledge intensive for which knowledge sharing is critical. Importance of knowledge sharing can he imagined from the findings that only Fortune 500 companies lose US $31.5 billion annually because of failure to share knowledge. Due to the importance of knowledge sharing for overall industries and especially for Software Engineering. there i"i always a need to look more rigorously into this aspect. Solhvarc Engineering itself is not a 1nature field yet and most of the studies done so far in this field have focused on the technical aspects. However. to encourage knowledge sharing, non-tcchnicaJ aspects (e.g. organizational, work environment. personality) are very crucial as well. Therefore. this study focused on work design characteristics.